Nanobiomaterials in dentistry : applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Applications of nanobiomaterials, 2016)
Nanobiomaterials in Dentistry: Applications of Nanobiomaterials discusses synthesis methods and novel technologies involving nanostructured bio-active materials with applications in dentistry. This book provides current research results for those working in an applied setting. The advantage of having all this information in one coherent text will be the focused nature of the chapters and the ease of which this information can be accessed. This collection of titles brings together many of the novel applications these materials have in biology and discusses the advantages and disadvantages of each application and the perspectives of the technologies based on these findings. At the moment there is no other comparable book series covering all the subjects approached in this set of titles.